Spin dephasing around randomly distributed vessels - Buschle, Lukas R.; Kurz, Felix T.; Schlemmer, Heinz-Peter; Ziener, Christian H. (Journal of magnetic resonance, 2019)
We analyze the gradient echo signal in the presence of blood vessel networks. Both, diffusion and susceptibility effects are analytically emphasized within the Bloch-Torrey equation. Solving this equation, we present the first exact description of the local magnetization around a single vessel. This allows us to deduce the gradient echo signal of parallel vessels randomly distributed in a plane, which is valid for arbitrary mean vessel diameters in the range of physiological relevant blood volume fractions. Thus, the results are potentially relevant for gradient echo measurements of blood vessel networks with arbitrary vessel size.
Available online 30 November 2018
Gesehen am 11.07.2019